THE EMERGENCE OF YOUTH VIOLENCE IN INDONESIA: A SOCIO-HISTORICAL ANALYSIS - Irfan Rifai (Islam Realitas: Journal of Islamic and Social Studies, 2016)
This qualitative exploratory study investigates the socio-historical context which impacts on the emergence of youth violence in an urban area, Jakarta, Indonesia. Research findings reveal how social and historical contexts impact youth’s propensity to conduct in youth violence. These social and historical contexts span from the local to the hybrid context; from the Indonesian traditional practices to the global trends of the youth’ social practices. This study illuminates the understanding that youth violence, particularly occurs in the urban area, is complex in nature and the study of youth violence should be placed in wider context. The result study It is widely known that this due to family-based tradition, that is, if one of the family has ever studied at this school, the other family members will follow studying at the same school as their ancestor did. This indicates that in fact parents and students are aware of what happens within the school including various practices of school culture. Studi eksplorasi kualitatif ini menyelidiki konteks sosio-historis yang berdampak pada munculnya kekerasan remaja di daerah perkotaan, Jakarta, Indonesia. Temuan penelitian mengungkapkan bagaimana sosial dan kecenderungan konteks sejarah dampak muda untuk melakukan kekerasan remaja. Ini konteks sosial dan historis span dari lokal ke konteks hybrid; dari praktek-praktek tradisional Indonesia dengan tren global praktek-praktek sosial pemuda’. Studi ini menerangi pemahaman bahwa kekerasan pemuda, terutama terjadi di daerah perkotaan, adalah kompleks di alam dan studi kekerasan remaja harus ditempatkan dalam konteks yang lebih luas. Hasil penelitian ini secara luas diketahui bahwa ini karena tradisi berbasis keluarga, yaitu, jika salah satu keluarga yang pernah belajar di sekolah ini, anggota keluarga yang lain akan mengikuti belajar di sekolah yang sama seperti nenek moyang mereka lakukan. Hal ini menunjukkan bahwa sebenarnya orang tua dan siswa menyadari apa yang terjadi di dalam sekolah termasuk berbagai praktik budaya sekolah.